Investigation on past human parvovirus B19 infection among blood donors in Xi 'an, China - ZHAO Boya; CHU Xiaoyue; JIN Yuqi; MA Chaofeng (Zhongguo shuxue zazhi)
[Objective] To investigate the distribution characteristics of previous infection of human parvovirus B19(HPV B19) among blood donors in Xi 'an, and to provide data support and theoretical basis for formulating individualized and precise blood screening strategies. [Methods] A total of 970 qualified blood samples tested at Shaanxi Blood Center from August to September 2024 were randomly selected. The levels of HPV B19 IgG antibodies in the serum were detected by enzyme-linked immunosorbent assay (ELISA). The distribution characteristics of the samples were analyzed from the perspectives of age, gender, education level, occupation, blood type and region. [Results] The positive rate of HPV B19 IgG antibodies among blood donors in Xi 'an was 25.26%(245/970), which increased gradually with age (P<0.05). There was no significant difference in the positive rate of HPV B19 IgG antibodies among blood donors of different genders, education levels, occupations, or blood types (P>0.05). Univariate logistic regression analysis showed that past HPV B19 infection was only related to age (P<0.05). The distribution of positive blood samples in 13 districts and counties of Xi 'an was counted based on the blood collection sites. The results showed that there was no significant global spatial autocorrelation in the distribution of positive samples. Among them, the Weiyang District and Beilin District exhibited a "high-high" cluster (P<0.05), while Chang'an District exhibited a "low-high" cluster (P<0.01). [Conclusion] A certain proportion of blood donors in Xi'an showed past infection with HPV B19, which was only correlated with age and demonstrated an upward trend. It is recommended to continue expanding the screening scope and incorporate screening for this virus in blood transfusion processes involving susceptible populations.